HYPONATREMIA: IS IT RELATED TO THE SEASONS? Hyponatremia and Seasons - Altuntaş, Atila (Journal of Medical Biochemistry, 2021)
Objectıve: Hyponatremia is a common electrolyte disorder in inpatients and related with morbidity and mortality. In this study we aimed to examine whether there is a relationship between incidence of hyponatremia among patients hospitalized in our nephrology department and the seasons. Material and Methods: Inpatients in our Nephrology Department between 2012-2015 were retrospectively analyzed. Patients with serum sodium levels below 135 mEq / L were included in the study. Hyponatremia incidence was calculated as the proportion of inpatients with low sodium levels in a season to total number of inpatients in the same season. Results: Out of 1950 inpatients in four-years period, 509 were found to have hyponatremia (26.1%). Mean serum sodium level of the patients was 129.7±4.7 mEq/L. Hyponatremia incidences in autumn, winter, spring and summer were found to be 28.7%, 15.4%, 20.4% and 36.6% respectively. Comparing the incidence of hyponatremia in patients hospitalized in winter and summer seasons, there was a significantly higher incidence of hyponatremia in summer (p <0.001). We found a positive correlation between hyponatremia incidence and temperature (r = 0.867, p = 0.001). However, there was a negative correlation between hyponatremia incidence and relative humidity (r =-0.735, p = 0.001). Conclusion: The highest hyponatremia incidence was observed in summer in four-year period. Loss of sodium by perspiration along with increased temperature and/or excessive hypotonic fluid intake might contribute to development of hyponatremia.